Implementasi Pengelolaan Arsip Statis Dan Dinamis Sesuai Konsep Record Life Cycle - Riyana Qori Fatmawati; Silvia Putri Yuliani; Zulfatun Sofiyani (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2026)
Records, as strategic information assets, play a vital role in supporting operational effectiveness, decision-making, and legal accountability; therefore, they require optimal management to ensure their authenticity is preserved over the long term. The implementation of static and dynamic records management is carried out at PT PLN (Persero) East Java and Bali Construction Division based on the records life cycle concept. This initiative focuses on optimizing records management through the stages of creation, distribution, use, maintenance, and final disposition. This activity was conducted using a participatory observation method over a one-month period to directly implement records management. The results of the implementation demonstrated improved orderliness in records management, efficiency in information retrieval, and strengthened authentication systems for both physical and digital records through the use of e-records technology. Additionally, more systematic management has led to enhanced organizational accountability and improved administrative governance quality. This initiative also contributes to enhancing archival competencies, thereby supporting the creation of a more reliable, effective, and sustainable archival system